Globalization and Personal and Global Identity in Colombian, Chinese, Hindu and American Students - Caycedo Espinel, Claudia Consuelo; Fundación Universitaria Konrad Lorenz (Pontificia Universidad Javeriana, 2009)
The main purpose of this study was to identify the relationship between status of personal identity and global identity, and between the experience of globalization and identity development in 717 college student of different nationalities i.e. Colombians, Chinese, Americans and Hindus. The measures used were EIPQ, the inventory of global identity, the experience factor of Globalization and the Inventory of identity distress. The analyses of results revealed significant relationships (Spearman Rho = 0.309, p = O, 01) between the Experiences of Globalization´s factor and the status of personal identity and significant relationships (Chi-square with significance level